Preference of University students towards cycling in campus - Raja Abdul Aziz, R.S. (2011)
Students have the potential for cycling, doing activities in and around campus. Nonetheless, bicycling is facing challenges that may reduce its attractiveness as compared to motorized modes. Weather, aggressive car driver, lack of cycling infrastructure, culture and social norm are some of the typical constraints that would discourage cycling in campus. All of these constraints should be considered in order to encourage students in university campus to cycle. However, a lot of factors can encourage students to cycling, such as the limitation of bus route, travel time, cost and individual physical condition. This paper presents the results and analysis on cycling preference as a possible transport mode in campus with the University of Malaya in Kuala Lumpur, Malaysia as a case study.